The Role Of The "Motherland" Concept In Different Nationalities And Cultures - Javliyev Mansurbek Odil o’g’li (Peerian Journals Publishing, 2024)
Modern Linguistics is undoubtedly one of the major branches of linguistics, which considers the extensive study of various conceptual, mental and anthropocentric problems in language as one of its urgent tasks. All over the world, different languages reflect the culture, mentality, national and ethnic image, values of different countries, and therefore, this language is an important tool that reflects the world view. At this point, the following words of the Russian scientist Vorkachev clarify the idea we are promoting. In his opinion, "Today, it is becoming a good tradition for the humanities to move away from the structuralist approach and enter the field of different knowledge."
Keywords: Modern Linguistics; various; knowledge